Investment impact of tax loss treatment: Empirical insights from a panel of multinationals - Daniel Dreßler; Michael Overesch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
We analyze the impact of tax loss treatment on the size and structure of multinational investments. Basically, two effects of tax loss treatment can be expected. First, firms make their investment decisions in the face of potential future losses. Then, the various types of conceivable loss offset provisions affect investment decisions. Secondly, existing loss carryforwards resulting from losses in the past affect the tax rate-elasticity of current investment decisions. The empirical analysis is based on data of German multinationals. The data is taken from the MiDi database provided by the German Central Bank (Deutsche Bundesbank). Regarding the tax loss treatment of potential future losses, our regression results suggest that a short carryforward time limit lowers investments in industries having a high probability to make losses. Moreover, we find significant positive effects of group loss offsetting provisions on the size of investments and on the number of subsidiaries they are structured across. Concerning the effects of existing losses carried forward, we find a reduced tax rate elasticity of investments for companies shielded by existing losses.
Keywords: F23; H25; H32; 330; Corporate Taxation; Loss Treatment; Group Taxation; Multinational Firms; Empirical Analysis; Unternehmensbesteuerung; Steuerbegünstigung; Steuerwirkung; Multinationales Unternehmen; Direktinvestition; Schätzung; Deutschland